Librarians as Teachers: Forming a Learning and Teaching Community of Practice. Issue 2 (3rd April 2017) - Osborn, Jennifer
Abstract: As liaison librarians embedded in the faculties and disciplines of the University of Adelaide, Learning and Research Services staff are working to significant changes in educational philosophies and practices. In 2016, we formed a Learning and Teaching Community of Practice (CoP), designed to ground our teaching of research skills and digital literacies in current pedagogy and new teaching methodologies. Our CoP was aligned with the university's commitment to 'Small Group Discovery Experience' teaching enhanced by the 'flipped classroom' model and new educational technologies. This article examines the benefits and opportunities created by our community of practice and considers options for future development.